Advokasi Migrant CARE dalam Kasus Perdagangan Manusia pada Pekerja Migran Indonesia di Malaysia (2022–2024) - Melissa Mulyawati Murni; Laode Muhammad Fathun (Pena Wimaya, 2026)
ABSTRACT The increasing number of Indonesian Migrant Workers in Malaysia during 2022–2024 is accompanied by a persistently high vulnerability to human trafficking, particularly among non-procedural workers. Although national regulations, bilateral cooperation, and regional frameworks exist, protection efforts remain limited due to weak coordination and cross-border law enforcement, indicating the limitations of state-based protection mechanisms and highlighting the importance of non-governmental organizations within transnational advocacy networks. This study aims to identify and describe the role of Migrant CARE in advocating human trafficking cases involving Indonesian Migrant Workers in Malaysia during the 2022–2024 period, using the Transnational Advocacy Networks (TANs) and human trafficking framework, which includes information politics, symbolic politics, leverage politics, and accountability politics. Using a descriptive-qualitative method through interviews and document analysis, the findings show that Migrant CARE plays a significant role in expanding protection by strengthening advocacy networks, elevating issues to the transnational level, and generating collective pressure. However, its optimization remains dependent on the political commitment of both countries and the consistency of cross-border law enforcement. Keywords: Migrant CARE; Human Trafficking; Indonesian Migrant Workers; Malaysia; Transnational Advocacy Networks